PEMGUATAN KARAKTER RELIGIUS SISWA DI SMP NEGERI 26 MAKASSAR - Imam Suyitno; Bakhtiar Bakhtiar; Fifi Kurniati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2022)
This study aims: 1) To determine the strategy of providing strengthening religious character education by teachers at SMP Negeri 26 Makassar. 2) To find out the factors that inhibit and support the provision of strengthening the religious character of students at SMP Negeri 26Makassar. 3) To find out the efforts taken by the teacher in overcoming the inhibiting factors. This type of research is a qualitative research using a descriptive approach. Data collection techniques include observation, interviews and documentation. The data obtained from the research results were processed using descriptive qualitative data analysi.The results of the study showed that (1) the strategy for strengthening religious character was carried out by teachers at SMP Negeri 26 Makassar, namely implementing strategies in the form of example, habituation, discussion stories using learning media. Using strategies in the form of rewards and punishments, and cooperation between teachers and parents or guardians of students. (2) factors that become inhibitors and supporters in the strategy of providing strengthening of religious character education at SMP Negeri 26 Makassar, namely the inhibiting factors are influenced by the environment, cellphone peers, self-awareness of the students themselves and the lack of teacher supervisors. While the supporting factors are the desire of students for supporting religious activities and adequate facilities and infrastructure. 3) The teacher's efforts in overcoming the inhibiting factors are holding cooperation with parents of students, giving advice and motivation to students in choosing friends to hang out with, limiting students from using mobile phones in class and raising students awareness and maximizing teacher supervision of students.